HISTORY TEACHING: THE USE OF PODCASTS FOR STUDENTS WITH VISUAL IMPAIRMENT (VERUM: Journal of Scientific Initiation, 2022)
This text emerges from the collection and analysis of part of the data from the research entitled “Teaching History: The Use of Podcasts for Students with Visual Impairment,” in the Professional Master’s in History at the Federal University of Rio Grande. The studies focus on the articulation of strategies and/or teaching resources in History education, specifically for students with visual impairments, as well as addressing the specific use of podcasts in History teaching. In this sense, the present research aimed to verify the presence and use of podcasts in educational spaces by History teachers. The final product to be articulated is the creation of a podcast about its functionality, especially regarding topics related to the classroom, special education, and inclusion, aimed at History teachers. Thus, the methodology used is action research, as it is characterized by seeking to understand situations, planning improvements, and explaining the results obtained. By proposing interviews with History teachers, with the intent for them to talk about their experiences with students with visual impairments, as well as whether podcasts are present in their classes, and how such a tool can aid in teaching students, we will be able to articulate new strategies for teaching History.
Keywords: History Teaching; Visual Impairment; Teaching Practices; Podcasts; Teacher Training